Milk productivity in Holstein cows from the dairy valley of Lima – Perú - Pallete P., Agustín (2023)
One of the main dairy areas in Peru is the valley of Lima, that has a maritime mild climate and has shown great livestock development in the latest decades. This study aimed to evaluate productive and reproductive characteristics of Holstein dairy cows in the Lima area. The data was obtained from The Official Milk Productivity Service (SOPL) Universidad Nacional Agraria La Molina. The total dataset of the research was 49125 lactations of Holstein cows belonging to 48 farms over a period of 1990 to 2000. The descriptive statistics show means and standard errors, the statistical model evaluated the effects of the year and number of calving on the milk production. The average results obtained were, lactation per campaign 7053 liters of milk with 334 days, lactation in 305 days with 7166 liters of milk. The reproductive characteristics were, age at first calving of 28 months, age at a maximum production of 72 months, the average age of 50 months, dry period of 82.3 days, and the interval between calving of 14.3 months. The effects of calving year and calving number showed a significant difference (P < 0.01) for all the productive and reproductive characteristics evaluated. Results indicate that the levels of dairy productivity in the Lima valley have increased through the 11 years in the study from 1990 to 2000, which show the great work carried out by farmers that contribute to the development of dairy livestock.